2022
DOI: 10.1136/bmjopen-2022-062051
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for the success and the feasibility of health mediation for healthcare use by underserved populations: a scoping review

Abstract: ObjectiveThis article aims to analyse the conditions under which health mediation for healthcare use is successful and feasible for underserved populations.MethodWe conducted a scoping review on the conditions for effective health mediation according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews standards. We searched for articles in the following databases: PubMed, PsychINFO, Scopus and Cairn published between 1 January 2015 and 18 December 2020. We se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Initially, HM focused on persons living with AIDS and mental health diseases, and then expanded to patients with other chronic conditions, but was not designed for FUEDs [ 16 , 23 ]. In our trial, 13.4% reported not having a GP, a slightly higher proportion than in the general population, and 24.3% had not seen a GP in the last three months, despite a higher prevalence of chronic diseases and a poorer quality of life than the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, HM focused on persons living with AIDS and mental health diseases, and then expanded to patients with other chronic conditions, but was not designed for FUEDs [ 16 , 23 ]. In our trial, 13.4% reported not having a GP, a slightly higher proportion than in the general population, and 24.3% had not seen a GP in the last three months, despite a higher prevalence of chronic diseases and a poorer quality of life than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…In their scoping review, Richard et al identified the conditions for the success and the feasibility of HM, in particular the status and training of HMrs [ 23 ]. They also noted that most papers took the effectiveness of HM for granted and only presented an analysis of the conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Long lacking a legal framework and professional benchmark, HM has been officially recognized in France by the law of modernization of the healthcare system in 2016, and defined in 2017 by the French National Authority for Health [ 33 ], as a set of actions to improve access to rights, prevention, and care, in order to promote health and thus move towards greater equity. Although HM has been widely promoted by the French Ministry of Health and many actors in the healthcare system, and its implementation has been evaluated in the context of health promotion and access to health in vulnerable people, tangible data on its effectiveness on access to health, quality and efficiency of health care in these populations are not available [ 30 , 38 40 ]. Although it seems entirely appropriate in the context of deprived frequent ED users, HM has never yet been tested or even evaluated in this context.…”
Section: Introductionmentioning
confidence: 99%
“…HM could respond to patients’ needs as they express it, respect their need for control over the situation, promote their ability to make their decisions, strengthen their sense of self-efficiency and their motivation to healthcare use. HM could also strengthen the ability to make decisions favourable to health in a logic of empowerment, and reinforce people’s perception of the healthcare benefits [ 40 ]. A HM intervention targeting deprived frequent ED users, starting in ED and consisting of education actions and navigation in care system could reduce readmissions to ED.…”
Section: Introductionmentioning
confidence: 99%
“…A committee of experts from outside the study reviewed the questionnaire. Questions and variables were standardized on previous PARCOURS studies, on precariousness scales and on the conceptual framework for describing CHW activities previously validated in the literature ( 12 , 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%